Adaptive Coping Strategies Positively Correlate with Maternal Knowledge among Low Birth Weight Infants - Tambunan, Eviana Sumarti; Malau, Paulus (Poltekkes Kemenkes Palu, 2025)
Uncertainty about newborn care can lead to stress and inadequate coping mechanisms in mothers of low-birth-weight (LBW) infants. This study aimed to assess mothers' knowledge of LBW infant care and its relationship with coping mechanisms. The study variables included maternal knowledge of LBW care and coping strategies. The study used a descriptive correlational design, with 90 mothers of LBW infants selected through purposive sampling. Data were collected using a questionnaire consisting of three sections: Coping Strategies Scale, the Maternal Knowledge Score, and demographic information. Statistical analysis was performed descriptively and inferentially using Pearson's correlation test. The results showed significant differences in LBW-care knowledge (p=0.02) and coping strategies (p=0.003). A significant correlation was found between maternal knowledge and coping strategies (r=0.242, p<0.015). This conclusion indicates that mothers with greater knowledge have better coping mechanisms. It is recommended that nurses provide proactive and engaging learning opportunities in health education programs on infant care to enhance the confidence and coping strategies of mothers with LBW infants..